ANSYS based Modal Analysis of a Fixed Beam of Uniform Cross Section with a Concentrated Mass at Mid Span - Bhandari, Abhishek; Chhetri, Akin; Luintel, Mahesh Chandra (Kathford Journal of Engineering and Management, 2023)
The report outlines ANSYS based modal and structural analysis of a fixed beam of dimension 20mm*20mm*1000mm that was constructed in SOLIDWORKS. Structural steel was selected as the material for analysis. The analysis was done in 3 phases, the first analysis was done without any crack and the other two analysis involved cracked beams with cracks created at different lengths. Suitable boundary and loading conditions were used to find the modes of frequencies. The resulting variation in static deflection, position of mode shapes representing transverse deflection and variation in position of equivalent stress corresponding to varying beam conditions with and without cracks are studied.